2022
DOI: 10.1155/2022/9947191
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin Attenuates Cisplatin-Induced Acute Kidney Injury by Inhibiting Ferroptosis

Abstract: Cisplatin is widely used in the treatment of solid tumors, but its application is greatly limited due to its nephrotoxicity; thus, there is still no effective medicine for the treatment of cisplatin-induced acute kidney injury (Cis-AKI). We previously identified that polydatin (PD) exerts nephroprotective effects by antioxidative stress in AKI models. Recent evidence suggests that oxidative stress-induced molecular events overlap with the process of ferroptosis and that there are common molecular targets, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…Recently, PD has been found to protect septic myocardial injury by promoting SIRT6-activated autophagy [19]. Our previous studies confirmed the renal protective effect of PD through antioxidative stress and antiferroptosis in I/R-induced AKI (I/R-AKI) and CP-AKI [4,9,11]. Based on the above evidence, we hypothesized that PD may attenuate CP-AKI through SIRT6-mediated autophagy.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Recently, PD has been found to protect septic myocardial injury by promoting SIRT6-activated autophagy [19]. Our previous studies confirmed the renal protective effect of PD through antioxidative stress and antiferroptosis in I/R-induced AKI (I/R-AKI) and CP-AKI [4,9,11]. Based on the above evidence, we hypothesized that PD may attenuate CP-AKI through SIRT6-mediated autophagy.…”
Section: Introductionsupporting
confidence: 59%
“…PD has also been verified to play a nephroprotective role by regulating autophagy in sepsis-induced AKI [5,6] and diabetic nephropathy [25]. In our last study, PD can alleviate CP-AKI by inhibiting ferroptosis [4], but whether autophagy is involved in the nephroprotection of PD on CP-AKI has not been reported yet.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Lu et al reported that Ras homolog enriched in brain could relieve cisplatin-induced AKI by maintaining mitochondrial homeostasis ( Lu et al, 2020 ). Zhou et al recently reported that polydatin enabled to attenuate the cell ferroptosis in cisplatin-induced AKI via regulating system Xc−/GSH/GPX4 pathway and inhibiting iron metabolism disorders ( Zhou et al, 2022 ). Deng et al found Se/Albumin nanoparticles could alleviate cisplatin-induced AKI by inhibiting ferroptosis with a decrease of superoxide dismutase, and up-regulation of GSH and GPX4 ( Deng et al, 2022 ).…”
Section: Ferroptosis Is Involved In the Development Of Akimentioning
confidence: 99%
“…ROS Detection in Kidneys. Dihydroethidium (DHE) was used to detect the ROS levels in the renal tissues, as previously reported [26]. The renal tissues were immersed in saccharose (30% w/v), embedded at the optimal cutting temperature (OCT), sliced into 5 μm sections, and stored at -20 °C until fluorescence detection.…”
Section: Determination Of Xo Activity and Expression In Serummentioning
confidence: 99%